2006
DOI: 10.1159/000091688
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nutritional Habits on Maternal-Neonatal Lipid and Lipoprotein Serum Levels in Three Different Ethnic Groups

Abstract: Aim: To investigate the effect of nutritional habits on lipid profiles in mothers of three different ethnic groups and in their newborns. Subjects and Methods: Lipids and lipoproteins were determined in 7-day dietetic diaries of 9,134 mothers (Greeks n = 3,118, Albanians n = 3,050, Muslim Asians n = 2,966), in their sera and in the cord blood of their newborns with routine methods. Results: Monounsaturated fat intake (35 ± 12 g/day) was similar among the groups. Total fat, saturated fat and cholesterol intakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…In a very recent study, it was reported that umbilical arterial lipids are more susceptible to peroxidation than umbilical venous lipids, indicating high oxidative stress in the fetal circulation irrespective of the mode of delivery (28). In this study, the absence of serious TAS reduction in the blood of the neonates, which also indicates the peroxidation of lipids, may be due to the presence of low levels of lipids, and, especially, to the very low LDL levels in the CB of the infants (36, 37), and/or the placenta protective effect against oxidative stress (4).…”
Section: Discussionmentioning
confidence: 55%
“…In a very recent study, it was reported that umbilical arterial lipids are more susceptible to peroxidation than umbilical venous lipids, indicating high oxidative stress in the fetal circulation irrespective of the mode of delivery (28). In this study, the absence of serious TAS reduction in the blood of the neonates, which also indicates the peroxidation of lipids, may be due to the presence of low levels of lipids, and, especially, to the very low LDL levels in the CB of the infants (36, 37), and/or the placenta protective effect against oxidative stress (4).…”
Section: Discussionmentioning
confidence: 55%
“…In a very recent study, it was reported that umbilical arterial lipids are more susceptible to peroxidation than umbilical venous lipids, indicating high oxidative stress in the fetal circulation irrespective of mode of delivery [40]. In this study, the absence of a very low TAS level in the blood of the neonates may be also due to the presence of low levels of lipids and especially to the very low LDL levels in the cord blood of the infants [41,42]. This finding is for first time reported in the literature but it needs further elucidation with a more specific method for lipid peroxidation evaluation such as electron spin resonance (ESR) [43].…”
Section: Discussionmentioning
confidence: 61%
“…The study flow is summarized in Figure 1. Data were extracted from 90 studies ( n = 126,242), 17–19,30,38,39,45–105 with 23 studies containing multiple dietary intake assessment points during pregnancy ( n = 4,985) 11,12,33–37,40,106–120 . The countries represented by geographical region are the USA (26 studies, n = 12,765)/Canada (5 studies, n = 143), UK (19 studies, n = 15,653), Europe (27 studies, n = 93,395), Australia (5 studies, n = 2,557)/NZ (2 studies, n = 291), and Japan (6 studies, n = 1,438).…”
Section: Resultsmentioning
confidence: 99%